A comprehensive review on functional roles of cancerous immunoglobulins and potential applications in cancer immunodiagnostics and immunotherapy - Heidari, Alireza; Peterson, Victoria (International Journal of Advanced Chemistry, 2020)
In this research, poly (D, L-lactide-co-glycolide)-block-poly (ethylene glycol), (PLGA-PEG) nanoparticles (NPs) of less than 195 nm in diameter containing of Naringenin (NRG) a naturally flavonoid were synthesized. Encapsulated form NRG improves its medical properties and solubility. The therapeutic efficacy of the encapsulated naringenin (NRG-NPs) and NRG on human lung epithelial (A549) and mouse mammary (4T1) carcinoma cells proliferation was determined by MTT assays. The cytotoxicity potency was rated as follows: NRG-NPs > NRG. The antioxidant effects of the NRG and NRG-NPs were also determined by FRAP method. Our results show that NRG-NPs are cytotoxic compounds for cancer cells and anti-cancer effect can be attributed to the presence of Fe chelatory and antioxidant effects of NRG-NPs.Â Â